The Case of Tweddle-Dee and Tweddle-Dum: authority control in a retrospective database - Chu, Clara; Green, Judith; MacDonald, Bertrum (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF